Return of individual research results: What do participants prefer and expect? - Sabina Sayeed; Robert Califf; Robert Green; Celeste Wong; Kenneth Mahaffey; Sanjiv Sam Gambhir; Jessica Mega; Bray Patrick-Lake; Kaylyn Frazier; Michael Pignone; Adrian Hernandez; Svati H Shah; et al. (PLoS ONE)
Newer data platforms offer increased opportunity to share multidimensional health data with research participants, but the preferences of participants for which data to receive and how is evolving. Our objective is to describe the preferences and expectations of participants for the return of individual research results within Project Baseline Health Study (PBHS). The PBHS is an ongoing, multicenter, longitudinal cohort study with data from four initial enrollment sites. PBHS participants are recruited from the general population along with groups enriched for heart disease and cancer disease risk. Cross-sectional data on return of results were collected in 2017-2018 from an (1) in-person enrollment survey (n = 1,890), (2) benchmark online survey (n = 1,059), and (3) participant interviews (n = 21). The main outcomes included (1) preferences for type of information to be added next to returned results, (2) participant plans for sharing returned results with a non-study clinician, and (3) choice to opt-out of receiving genetic results. Results were compared by sociodemographic characteristics. Enrollment and benchmark survey respondents were 57.1% and 53.5% female, and 60.0% and 66.2% white, respectively. Participants preferred the following data types be added to returned results in the future: genetics (29.9%), heart imaging, (16.4%), study watch (15.8%), and microbiome (13.3%). Older adults (OR 0.60, 95% CI: 0.41-0.87) were less likely to want their genetic results returned next. Forty percent of participants reported that they would not share all returned results with their non-study clinicians. Black (OR 0.64, 95% CI 0.43-0.95) and Asian (OR 0.47, 95% CI 0.30-0.73) participants were less likely, and older participants more likely (OR 1.45-1.61), to plan to share all results with their clinician than their counterparts. At enrollment, 5.8% of participants opted out of receiving their genetics results. The study showed that substantial heterogeneity existed in participant's preferences and expectations for return of results, and variations were related to sociodemographic characteristics.